2010
DOI: 10.1021/ie101328m
|View full text |Cite
|
Sign up to set email alerts
|

DNA Coiled Coil Superstructures in Oligonucleotide Crystals

Abstract: We present the structure of coiled coils found in two oligonucleotide DNA crystals. The sequences d-(ATATATATAT) and d(CGATATATAT) are used. In the first case several coiled coils with different structures are found. In the second case a single structure is present. The results are compared with other coiled coil structures. They might be used in the development of new nanomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Another feature of these columns is that the angle of the axis of each duplex with respect to the overall axis of the column is 9 . Thus, the duplexes are organized as a smooth coiled coil (De Luchi et al, 2011), as shown in Fig. 5.…”
Section: Dna Structurementioning
confidence: 99%
“…Another feature of these columns is that the angle of the axis of each duplex with respect to the overall axis of the column is 9 . Thus, the duplexes are organized as a smooth coiled coil (De Luchi et al, 2011), as shown in Fig. 5.…”
Section: Dna Structurementioning
confidence: 99%
“…The coiled coils can be considered as regularly bent HASO structures. Their dimensions can be exactly calculated from the diffraction pattern, as described elsewhere . It has a radius of 10.6 Å and a pitch of 503 Å equivalent to 13 dodecamers per helical turn.…”
Section: Resultsmentioning
confidence: 99%
“…Their dimensions can be exactly calculated from the diffraction pattern, as described elsewhere. 32 It has a radius of 10.6 Å and a pitch of 503 Å equivalent to 13 dodecamers per helical turn. A model of the structure is presented in Figure 4.…”
Section: Form III (Coiled Coil)mentioning
confidence: 99%
“…The average helical twists ω for the step with one Mg 2+ is -31.42 • whereas for the step with two Mg 2+ it is -26.66 • . The kink angle (De Luchi et al, 2011) between stacked oligonucleotides (Ω) is about 170 • and the average bending of oligonucleotides is about 6.43 • with the major bending in the GC step. The minor groove in the central region widens as a result of bending.…”
Section: Structures Comparisonmentioning
confidence: 99%